The economics of COVID-19 - Baltagi, Badi H.; Moscone, Francesco; Tosetti, Elisa (Bingley, U.K. : Emerald Publishing Limited, 2022)
The global health crisis, exacerbated by the COVID-19 outbreak, has challenged all sectors of society, including health, economics, finance, and social inequality. The threats and complexities from the COVID-19 pandemic shock are the core subject of this latest volume in the Contributions to Economic Analysis series. The Economics of COVID-19 contains selected contributions analysing the effects of this pandemic, covering macroeconomics, computable general equilibrium models, financial markets, the reduction in seismic noise due to the slowdown in traffic and economic activities caused by the spread of the virus, the rapid surge in the digital transformation of production and consumption. Also included are health studies proposing to improve the traditional epidemic models, the effects of the pandemic on mental health, Minority Ethnic Groups in the UK, as well as the Lombardy region in Italy. The aim of this collection is to spur much needed research into the effects of COVID on the global economy, the health, and financial sectors, as well as its effects on development and growth and economic inequality.
Chapter 1. Understanding economic instability during the pandemic: A factor model approach / Monica Billio, Roberto Casarin, and Fausto Corradin -- Chapter 2. General equilibrium analyses of covid-19 impacts and policies: An historical perspective / Roberto Roson and Camille Van der Vorst -- Chapter 3. The relationship between covid-19 and the financial market / Daniele Massacci -- Chapter 4. Exploring the economic effects of covid-19 in the United States through the seismograph / Luca Tiozzo Pezzoli and Elisa Tosetti -- Chapter 5. Covid-19 and digital economy: The journey towards a digital transformation in new normal: How to prepare for the future / S. Asieh Hosseini Tabaghdehi -- Chapter 6. Estimating uncertainty in epidemic models: An application to covid-19 pandemic in Italy / Giuseppe Arbia, Vincenzo Nardelli, and Chiara Ghiringhelli -- Chapter 7. The effects of the pandemic on mental health / Cinzia Rienzo -- Chapter 8. Ethnicity and inequality during the covid-19 pandemic in the uk / Catia Nicodemo, Stuart Redding, and Joan Madia -- Chapter 9. The impact of covid-19 pandemic on the healthcare system in lombardy / Marta Angelici, Paolo Berta, and Giorgio Vittadini.
Includes bibliographical references and index.
Print version record.
Keywords: elektronické knihy; electronic books; COVID-19 Pandemic, 2020- -- Economic aspects; International economic relations; Business & Economics -- International -- Economics; International economics